THE CONSTRUCTION OF MURTADHA MUTAHHARI’S THOUGHT REGARDING DIVINE WILL AND HUMAN’S WILLING - Fathurrahman Fathurrahman (JICSA : Journal of Islamic Civilization in Southeast Asian, 2019)
This article discusses the thoughts of Mutahhari Mutahhari about Divine Will and Human Will, Research Objectives, To know and understand how the construction of the Divine will and human will in the view of Mutahhari Murtadha. This type of research is a descriptive qualitative research. The approach used is a philosophical approach, but the philosophical approach used in this thesis is the Islamic philosophical approach (disposition). The data source is divided into two, namely primary data sourced from Motahhari's works and secondary data which are related to Motahhari's thoughts. Data processing and analysis techniques are done by using the process of arranging data sequences, organizing them in a pattern, category and basic description units, and the data analysis used in this study is qualitative analysis, this method is intended that the analysis departs from the data and leads to conclusions General research results show that there is a link between the Divine will and the human will, where both (Divine will and Human will) are not in conflict. The Divine Will in this case the Divine destiny does not confine man and destroys it even it is Divine destiny that makes man free and independent in choosing what he wants.